Respuesta :

Write an equation based on the problem
For an instance, x is the previous weight
"After losing 30 pounds" could be written as (x - 30)
"110 pounds more than one-third his previous" could be written as (110 + [tex] \frac{1}{3} [/tex]x)

Join the expression and solve for x
x - 30 = 110 + [tex] \frac{1}{3} [/tex]x

Move 1/3 x to the left side, and the constant of 30 to the right side, so like terms will be on equal side
x - [tex] \frac{1}{3} [/tex]x = 110 + 30

Equalize the denominators of the fractions
[tex] \frac{3}{3} [/tex]x - [tex] \frac{1}{3} [/tex]x = 140
[tex] \frac{2}{3} [/tex] = 140
x = 140 × [tex] \frac{3}{2} [/tex]
x = 420/2
x = 210

The previous weight was 210 pounds
The new weight is 210 - 30 = 180 pounds